Pengaruh Estetika Desain terhadap Persepsi Merek dan Keputusan Pembelian Konsumen di Pasar Internasional - Rizky Fiqran Pratama (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2025)
The study aimed to examine the importance of product design aesthetics in influencing consumer brand perception and brand purchasing behavior in a culturally diverse market. Using a mixed methods approach, the researchers obtained quantitative data through questionnaires distributed to 300 respondents selected through stratified random sampling from three leading economies (USA n=100, Germany n=100, Japan n=100). Multivariate regression analysis showed a significant positive effect of aesthetics on brand equity formation (β=0.71, p<0.001; R²=0.42), explaining up to 42% of the variance in purchase intention. The results showed significant cultural differences in design preferences: 73% of Western consumers (USA: 75%, Germany: 71%) favored more minimalist designs, with monochrome & geometric trends; while 68% of Japanese respondents favored polychromic arrangements with detailed symbolic components. Rather than a uniform global product design paradigm, these findings suggest a flexible conceptual framework of the Cultural Design Adaptation Matrix (CDAM). The CDAM paradigm systematizes assets into four strategic dimensions: color semiotics, form-language localization, symbolic value alignment, and tactile experience customization and it is known that multinational companies can increase market penetration by 18-22% by modifying culture-specific design elements, while the theoretical contributions expand our knowledge of aesthetic cognition in cross-cultural consumer behavior.